G181 Successful implementation of a paediatric community home nursing service as a model of service delivery in acute paediatric care. (7th April 2014) - Ng, SM; Mariguddi, S; Coward, S; Middleton, H
Abstract : Aims and objectives: The aim of this pilot service development was determine if Community Children's Nursing Outreach Team (CCNOT) service as a model of care was effective and efficient in its delivery of reducing unscheduled care and admissions of paediatric patients into hospital and improving patient satisfaction. Design: This is a pilot prospective study within a dual-site integrated care organisation. Methods: The CCNOT service was developed with an aim to determine the effectiveness of the CCNOT model of care and service delivery in the following outcomes: 1) reducing length of hospital stay 2) reducing Accident and Emergency admissions 2) reducing non-elective admissions 3) reducing readmissions and 4) improving patient satisfaction. Data was obtained from Hospital Episode Statistics (HES) and patient satisfaction questionnaires. Results: The data indicates that following the implementation of the service, paediatric A&E attendances had reduced by 5% per month, non-elective admissions had reduced by 15.8%, number of readmissions had reduced by 17.3% and the overall LOS was increased by 2.3%. The results of the patent satisfaction survey shows overall a high patient satisfaction for the service. Conclusions: Paediatric CCNOT service as a model of service delivery in in acute paediatric care is effective in reducing hospital admissions and increases patient and carer satisfaction with care provision for sick children in the home environment. Paediatric community home nursing should be implemented with nurses trained in paediatrics and with clear clinical governance, pathways and robust documentation. Delivering acute care within the community such as community home nursing service may reduce demand for unscheduled care and reduce the financial cost to the National Health Service in UK.